Software Design for Smile Analysis - A. Sodagar; R. Rafatjoo; D. Gholami Borujeni; H. Noroozi; A. Sarkhosh (Tehran University of Medical Sciences, 2010)
Introduction: Esthetics and attractiveness of the smile is one of the major demands in contemporary orthodontic treatment. In order to improve a smile design, it is necessary to record "posed smile" as an intentional, non-pressure, static, natural and reproducible smile. The record then should be analyzed to determine its characteristics. In this study, we intended to design and introduce a software to analyze the smile rapidly and precisely in order to produce an attractive smile for the patients. Materials and Methods: For this purpose, a practical study was performed to design multimedia software "Smile Analysis" which can receive patients' photographs and videographs. After giving records to the software, the operator should mark the points and lines which are displayed on the system's guide and also define the correct scale for each image. Thirty-three variables are measured by the software and displayed on the report page. Reliability of measurements in both image and video was significantly high (α=0.7-1). Results: In order to evaluate intra- operator and inter-operator reliability, five cases were selected randomly. Statistical analysis showed that calculations performed in smile analysis software were both valid and highly reliable (for both video and photo). Conclusion: The results obtained from smile analysis could be used in diagnosis, treatment planning and evaluation of the treatment progress.